Finite element modeling and effects of material uncertainties in a composite laminate with bend–twist coupling. (March 2015) - Murray, Robynne E.; Doman, Darrel A.; Pegg, Michael J.
Abstract: Finite element models (FEMs) are used in the design of composite bend–twist (BT) coupled structures such as tidal turbine blades and marine propellers. However, such design tools must be verified experimentally. This paper presents the experimental verification of a composite FEM by static bending tests of 500 × 200 mm BT coupled laminate plates. It was found that the FEM accurately predicted the test sample deformation, and the bending and twisting response of the samples were linear within the range of applied loads. The sensitivity of the FEM to model inputs and manufacturing accuracy was explored, and it was found that the laminate thickness and accuracy of ply angles were highly influential on the ability of the FEM to predict accurate deformations.